Influence of firm size, profitability, and leverage on firm value: the moderating role of managerial ownership in IDX property and real estate - Anjelika, Anjelika; Santoso, Hadi (Institute of Computer Science (IOCS), 2025)
The study examines the relationship between firm size, profitability, and leverage and firm value, while incorporating managerial ownership as a moderator in property and real estate companies, specifically the IDX. The research utilised a purposive sampling technique, which produced 145 sample observations from 29 companies within the property and real estate sector spanning 2020–2024. Data processing was conducted using the EViews 13 application. The investigation applied panel data regression techniques for analytical purposes and used the MRA (Moderated Regression Analysis) approach to examine moderating influences. The study indicates that firm size and profitability contribute positively and significantly to firm value, in contrast to leverage, which exerts an adverse and insignificant impact. Managerial ownership exhibits an apparent moderating effect on the relationship between company size and corporate value. At the same time, no such moderating effect is detected in the influence of profitability and leverage on firm value. These findings can serve as practical implications for company management and investors in formulating strategies to enhance firm value, while also enriching the academic literature as a foundation for future research